Understanding and shaping curriculum : what we teach and why - Hewitt, Thomas W. (Sage, 2006)
Hewitt introduces audiences to curriculum as knowledge curriculum as work, and curriculum as professional practice. This text not only acquaints readers with the study of curriculum, but also helps them to become effective curriculum practitioners.